Working process of the community health workers in vulnerability areas: Working process of the community health workers - Vanda Nayara Costa da Silveira; Rayane Moreira de Alencar; Jameson Moreira Belém; Camila de Araújo Carrilho; Evanira Rodrigues Maia (Journal of Health Care, 2023)
Introduction: The Community Health Agents act by promoting dialogue between the health needs of the community and the Family Health Strategy. This context, or work process of these professionals, is directly related to the dimensions of the territory and its vulnerabilities. Objectives: to understand the work process of Community Health Agents in territories of vulnerability enrolled in the Family Health Strategy. Materials and Methods: This is a qualitative study, subsiated by the theoretical framework of health vulnerabilities, conducted with 11 Community Health Agents, who worked in a vulnerable area located in the central region of Ceará, northeastern Brazil. Data were collected through semi-structured interviews, containing the work process. Results: Three thematic categories emerged representing the dimensions of health vulnerability, which address the main topics discussed by the participants: (1) "We are the link between people and the health center": the relationship of the Community Health Agent with the community (2) "You expose yourself": the Community Health Agent and its working conditions; 3) "Blind, deaf and dumb": the community health agent in the face of violence and drug trafficking in the community. Conclusion: The work process of the Community Health Agent in territories of vulnerability was affected in the individual, social and programmatic dimensions.